2017
DOI: 10.1039/c7ra04994c
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-mediated synthesis of sugar–PEG-based amphiphiles for encapsulation and stabilization of indocyanine green

Abstract: Bio-catalytically synthesized sugar–PEG-based copolymers form stable micelles in an aqueous medium. These micelles from amphiphilic copolymer are able to efficiently solubilize and stabilize indocyanine green dye (ICG) under physiological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Sugar-polyethylene glycol amphiphilic copolymers were synthesized using N435 as a catalyst for the transesterification, introducing decanoic and myristic acids. 370 D-Fructose (99%) and D-glucose (34%) were modified with 2,2,2-trifluoroethyl methacrylate in tert-butanol using N435, and methacryloyl-D-fructose was polymerized using as the crosslinker ethylene glycol dimethacrylate. 371 Glycerolysis of certain oils are also important to get monomers useful in polymer production.…”
Section: Lewatit Vp Oc 1600mentioning
confidence: 99%
“…Sugar-polyethylene glycol amphiphilic copolymers were synthesized using N435 as a catalyst for the transesterification, introducing decanoic and myristic acids. 370 D-Fructose (99%) and D-glucose (34%) were modified with 2,2,2-trifluoroethyl methacrylate in tert-butanol using N435, and methacryloyl-D-fructose was polymerized using as the crosslinker ethylene glycol dimethacrylate. 371 Glycerolysis of certain oils are also important to get monomers useful in polymer production.…”
Section: Lewatit Vp Oc 1600mentioning
confidence: 99%
“…In these cases, the result is the photosensitizer encapsulated and stabilised in aqueous media inside the micelle. 142,143 In other studies, the photosensitizer can be encapsulated in the micelles during the same micelle formation process. 144 Liposomes reflected in the high number of studies and formulations that can be found in the literature.…”
Section: B Organic-based Nanostructuresmentioning
confidence: 99%
“…However, the application of ICG for clinical imaging and therapeutic applications has several limitations, such as a short plasma half-life and poor aqueous stability. Various trials including nanoformulations of ICG [ 84 , 85 ] or sugar conjugation of ICG [ 86 , 87 , 88 ] have been developed to overcome these limitations.…”
Section: Other Expected Photosensitizersmentioning
confidence: 99%